ANALISIS DAMPAK SUBSIDI PANGAN (RASKIN) TERHADAP TINGKAT PENDAPATAN RUMAH TANGGA DAN SEKTOR PEREKONOMIAN INDONESIA (Pendekatan Analisis SNSE Indonesia Tahun 2008) - Ruben B.R. Silaban; Achma Hendra Setiawan (Diponegoro Journal of Economics, 2013)
Food is a very important topic, because it includes the social, political and economic significance, it is not separated from the definition of the concept of food as one of the basic needs of every individual and is one of the main pillars of human rights. Government is obliged to ensure food security, in terms of number of good qualities and price stability and on the other hand, an increase in income to boost purchasing power, especially from low-income groups. One example of government policy relating to the above context is to give food subsidies. Food subsidies given in the form of providing cheap rice for the poor through rice special market operations by Bulog. Food subsidies aimed at ensuring the availability and distribution of rice and price stability by providing affordable prices to the poor or low income groups. This research’s purpose is to analyze the effects of the realization of food subsidies on household income levels and sectors of the Indonesian economy. To analyze the impact of food subsidies on household income levels and sectors of the Indonesian economy, this study used an analysis tool SAM (Social Accounting Matrix) which is based on the approach chart Social Accounting Matrix (SAM) Indonesia 2008. The result of this research found that the Food Subsidy will have an impact on increasing household income in Indonesia amounted to 0.86 percent, from Rp. 2,450,888.53 billion changed to Rp. 2,472,062.68 billion. Group of households with the highest income level changes is a sector group of households receiving food subsidies by raising revenue by 5.29 percent, from Rp. 298,165.08 billion changed to Rp. 313,939.76 billion. The second highest income increase is agricultural employers household by 0.32 percent, from Rp. 703,950.96 billion to Rp. 706,191.88. Sectors of the economy which have the greatest increase in productivity as a direct and total economic impact of food subsidies (Raskin) is the food industry, beverages and tobacco.